(untitled) (World Science, 2018)
The problems of designing children’s preschool institutions in Ukraine are related to the need for pre-school education services to be broadly covered by children. The Government of Ukraine, and in particular the Ministry of Education, raised the issues of development and improvement of the quality of education in our country to the most urgent tasks. General education and informatization of Ukrainian society, growth of educational potential of the population, focus on increasing the amount of knowledge, starting with early childhood – all these and other provisions and directions of the development of domestic education should be reflected in the researches of Ukrainian scientists, including in the architectural and urban aspects. The consolidation of urban development, the lack of free areas for construction in prevailing urban areas, the proliferation of high-rise housing construction, the overcrowding of kindergartens puts an urgent issue in the development of new design solutions for preschool institutions built-in-type. In this sense, the priority task is the analysis of existing scientific research in the field of designing this type of preschool institutions.